Set theoretic approach to the concept of net sensitivity and net specificity in screening test results - Mukhopadhyay, Bansi Badan; Bhattacharjya, Himadri (International Journal Of Community Medicine And Public Health, 2018)
Net sensitivity and net specificity have been reviewed from set theoretic approach. With a basic knowledge of set theory one can estimate the net sensitivity and specificity in an easy way in both sequential and simultaneous screening tests. Union, intersection and complementary operations of set theory have been adopted to find out the solutions.